A note on an inequality of Bourgain and Brezis. (March 2016) - Zhang, Zhibing
Abstract: In this note, we give a new and elementary approach to an inequality of Bourgain and Brezis (2007) for L 1 vector fields, avoid using the Littlewood–Paley decomposition that Bourgain and Brezis used. And we also give an equivalent version of the inequality. Highlights: A new and elementary proof to an inequality of Bourgain and Brezis is given. Avoid using the Littlewood–Paley decomposition. An equivalent version of the inequality is given.